2009
DOI: 10.11646/zoosymposia.2.1.28
|View full text |Cite
|
Sign up to set email alerts
|

<p class="HeadingRunIn"><strong>Variable modes of larval development in the <em>Polydora cornuta</em> complex (Polychaeta: Spionidae) are directly related to stored sperm availability</strong></p>

Abstract: Reproductive crosses between geographically separated populations of the nominal species, Polydora cornuta, support the hypothesis that the Florida/ Gulf of Mexico populations represent a single, potentially interbreeding lineage that is reproductively isolated from West Coast (California) and East Coast (Carolinas to Maine) populations. Previous research has indicated that California populations are reproductively compatible with worms from North Carolina but reproductively isolated from Maine populations. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…There is, however, increasing evidence demonstrating the flexibility in larval developmental mode in polydorids. For example, an increase in nurse egg production accompanied by a decrease in numbers of adelphophagic larvae per brood occurred in response to sperm limitation in Polydora cornuta (Rice & Rice, 2009) or an increase in latitude for Boccardia proboscidea (Oyarzun et al , 2011) while the opposite effect occurred when female B. proboscidea were exposed to bisphenol A (Hart et al , in Gibson et al , 2012). It is therefore possible that the poecilogony demonstrated by David et al (2014) and Simon (2015) was induced by environmental conditions unique to South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, increasing evidence demonstrating the flexibility in larval developmental mode in polydorids. For example, an increase in nurse egg production accompanied by a decrease in numbers of adelphophagic larvae per brood occurred in response to sperm limitation in Polydora cornuta (Rice & Rice, 2009) or an increase in latitude for Boccardia proboscidea (Oyarzun et al , 2011) while the opposite effect occurred when female B. proboscidea were exposed to bisphenol A (Hart et al , in Gibson et al , 2012). It is therefore possible that the poecilogony demonstrated by David et al (2014) and Simon (2015) was induced by environmental conditions unique to South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the differences that we found on feeding capacities among larvae, which allow Type A larvae to advance in development inside a capsule and hatch as juveniles, the presence of greater numbers of nurse eggs could potentially reduce the probabilities of cannibalism on Type B larvae, increasing their chances of hatching as planktotrophs. According to Smith & Gibson (1999) and Gibson et al (2012), production of nurse eggs in B. proboscidea and P. cornuta form through an active process that resembles apoptosis (but see Rice & Rice 2009). Females of B. proboscidea therefore have the potential to adjust the proportion of larvae that will hatch as advanced larvae or juveniles versus larvae that will hatch as planktotrophs by manipulating the number of nurse eggs inside capsules, or by limiting the ingestion of nurse eggs and siblings by adjusting the hatching time (Oyarzun & Strathmann 2011).…”
Section: Discussionmentioning
confidence: 99%
“…According to Smith & Gibson () and Gibson et al. (), production of nurse eggs in B. proboscidea and P. cornuta form through an active process that resembles apoptosis (but see Rice & Rice ). Females of B. proboscidea therefore have the potential to adjust the proportion of larvae that will hatch as advanced larvae or juveniles versus larvae that will hatch as planktotrophs by manipulating the number of nurse eggs inside capsules, or by limiting the ingestion of nurse eggs and siblings by adjusting the hatching time (Oyarzun & Strathmann ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rasmussen (1973) found that differences in the development pattern of Pygospio elegans Clapar ede were related to environmental factors and were not genetically inherent in a population. In populations of Polydora cornuta complex, the variability in larval size results from the limitations concerning the level of stored sperm in seminal receptacles of the female, rather than being a genetically determined reproductive strategy (Rice & Rice 2009). Type II: capsules of eggs with only adelphophagic larvae; Type III: capsules of eggs with both kinds of larvae.…”
Section: Discussionmentioning
confidence: 99%